2014
DOI: 10.3389/fphar.2014.00281
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of maternal ingestion of cocoa upon fetal ductus arteriosus in late pregnancy

Abstract: Cocoa powder has twice more antioxidants than red wine and three times more than green tea. Ten percent of its weight is made up of flavonoids. Cocoa has antioxidant and anti-inflammatory effects by downregulating cyclooxigenase-2 receptors expression in the endothelium and enhancing nitric oxide bioavailability. There are evidences that while polyphenols ingestion have cardioprotective effects in the adult, it may have deleterious effect on the fetus if ingested by the mother on the third trimester of pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Lastly, as shown in the introduction, the anti-inflammatory and antioxidant properties of polyphenols induced alterations in the closure dynamics of the fetal ductus arteriosus when consumed in high amounts during the third trimester of pregnancy, which is the critical window of development of the fetus’ ductus [ 27 , 28 , 87 ]. Similarly, we have demonstrated that maternal naringin supplementation during the third week of gestation induced redox alterations in the offspring’s brain, mainly on postnatal day 7, which promoted a sex-dependent pro-oxidative milieu in the cerebellum and striatum at this postnatal age.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, as shown in the introduction, the anti-inflammatory and antioxidant properties of polyphenols induced alterations in the closure dynamics of the fetal ductus arteriosus when consumed in high amounts during the third trimester of pregnancy, which is the critical window of development of the fetus’ ductus [ 27 , 28 , 87 ]. Similarly, we have demonstrated that maternal naringin supplementation during the third week of gestation induced redox alterations in the offspring’s brain, mainly on postnatal day 7, which promoted a sex-dependent pro-oxidative milieu in the cerebellum and striatum at this postnatal age.…”
Section: Discussionmentioning
confidence: 99%
“…122 An experimental single-dose of cocoa administered to rats during the third trimester of gestation caused ductal constriction equivalent to that caused by indomethacin. 123 Normal human fetuses during the third trimester, when exposed to maternal consumption of polyphenols above the 75 th percentile of the average population, exhibit worse ductus arteriosus flow dynamics and increased right-to-left ventricular diameter ratios (higher ductal flow velocities and larger right ventricular diameters), in comparison with those exposed to maternal consumption of polyphenols below the 25 th percentile. 76 Normal human fetuses submitted to guided nutritional intervention (restriction of polyphenol-rich foods) in the third trimester showed, after 2 weeks, decreased ductal systolic and diastolic velocities, increased pulsatility index, and decreased right-to-left ventricular and pulmonary artery to aorta ratios, whereas these parameters did not change during the same period in control fetuses who were not submitted to the intervention.…”
Section: Fetal Ductal Constriction: Treatment and Preventionmentioning
confidence: 99%
“…An experimental single-dose of cocoa administered to rats during the third trimester of gestation caused ductal constriction equivalent to that caused by indomethacin. 123…”
Section: Fetal Ductal Constriction: Treatment and Preventionmentioning
confidence: 99%
“…Premature intra-uterine DA constriction could be diagnosed in complex congenital heart malformations, including Tetralogy of Fallot and truncus arteriosus. As an isolated defect, it is usually secondary to the use of medication like NSAIDs, isoxsuprine, fluoxetine and some foods rich in polyphenol like herbal teas, dark chocolate, orange juice, red/purple grapes, berries and coffee [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%